Manpower Projections : Atlantic Canada, Some Policy Considerations - Jain, Harish C. (Relations industrielles / Industrial Relations, 1969)
This article attempts to describe, briefly, the present manpower situation in the Atlantic Region of Canada vis-a-vis the policies pursued by the federal and provincial government agencies in connection with the manpower problems of the region. Our purpose is twofold: First, to state reasons for the necessity of forecasting manpower requirements at the regional level and the relevance of manpower projections to the problems of manpower utilization. Second, to describe the methodology of forecasting manpower requirements and training needs for the Nova Scotia Department of Labour to illustrate what can and needs to be done at the regional level. Research and data gaps in the forecasting of manpower requirements and supply along with some concluding remarks form the evaluative part of this article.